Integrating orange-fleshed sweetpotato in Zambia (Oct 2011- Sept 2015). - Chipungu, Felistus P. (International Potato Center, 2015)
This flyer is a summary of the objectives, achievements, lessons learnt and future plans of a four year project that aimed to improve vitamin A and energy intake for at least 15,000 rural households growing and consuming OFSP, of which 75% should be women with children under 5 years of age. Supported under USAID’s Feed the Future (FTF) initiative, it also sought to improve overall household food security and diet diversification through effective dissemination of pro-vitamin A rich OFSP varieties and improved production, conservation, and utilization techniques linked to increased nutritional knowledge.